MONITORING IN HIGHER EDUCATION: THE ROLE IN FORMATION OF NATIONAL MANPOWER POLICY OF UKRAINE - Bobrytska, Valentyna (Proceedings of National Aviation University (archive), 2015)
The author defines the understanding of monitoring in higher education as a special system for the collection, processing, storage and dissemination of information on the state of higher education, the prediction of objective data of the dynamics, the main trends of higher education development, the development of evidence-based recommendations for management decisions in improving the efficiency of higher education as the starting point of the research. It is determined that the main purpose of using the results of monitoring in higher education is to establish the correspondence of the educational services level (and thus the teaching staff quality assurance) and the needs of society at the present stage of its development. The paper characterizes the formation of the national manpower policy of Ukraine in the sphere of higher education on the basis of information on the quality of higher education, in particular on the results of the international rankings of the best world universities, the objective data of the dynamics and status of training of specialists with higher education in Ukraine. Based on monitoring studies of capabilities of the national system for teaching and scientific staff training for higher education we distinguish a group of factors that determine the conditions of effective implementation of manpower policies in this field: 1) taking into account the demographic situation; 2) the creation of an effective system of multichannel financing of higher education; 3) the investment policy of the government in the field of higher education; 4) improvement of public employment policy; 5) development of pricing in the field of education; 6) settling political and legal factors in training for higher education; 7) taking into account national peculiarities of higher education in the emerging knowledge society, integration in the European Higher Education Area and European Research Area.